Prevention of False-Positive Results: Development of an HPTLC Autographic Assay for the Detection of Natural Tyrosinase Inhibitors - Taibon, Judith; Ankli, Anita; Schwaiger, Stefan; Magnenat, Camille; Boka, Vasilik-Ioanna; Simões-Pires, Claudia; Aligiannis, Naktarios; Cuendet, Muriel; Skaltsounis, Alexios-Leandros; Reich, Eike; Stuppner, Hermann (Planta Medica, 2015)
A simple and rapid high-performance thin-layer chromatography-based autographic assay was established to screen plant extracts for the presence of tyrosinase-inhibiting substances. Three mobile phases were selected for the chromatographic separation of different types of extracts. After development, the plate was sprayed with the substrate solution Levodopa followed by a solution of the enzyme tyrosinase. Several known tyrosinase inhibitors were tested simultaneously as positive controls. They were detected as white spots with white light in remission from the plate as well as with white light transmitted through the plate. Some of the investigated extracts included spots showing a different behaviour; some lipophilic substances appeared as white spots in white light remission but were black in white light transmission. This behaviour, which could lead to false-positive results, was due to poor wettability of the corresponding spots. False-positive results were eliminated by adding Triton X-100 to the Levodopa solution and drying the plate after 10 minutes incubation with a molecular sieve. Tyrosinase inhibitors can be clearly identified as white spots against a dark background in white light remission as well as in white light transmitted through the plate. The established high-performance thin-layer chromatography autographic assay was validated and can be used as a standard method for the detection of tyrosinase inhibitors in plant extracts without causing false-positive results.
Keywords: autographic assay; HPTLC-MS; tyrosinase inhibitors; false positive results